Health Effects of Trade Liberalization: Evidence from US Counties - Navaei, Amirhooshang; Farnoud, Farhad (European Journal of Multidisciplinary Studies, 2021)
This paper explores the potential externality of trade liberalization between the US and China on air pollution and infants’ health outcomes. Exploiting the differential impact of tariff reductions due to trade liberalization across industries combined with compositional variations of industry-specific employment across counties as the main source of identification strategy and using the universe of birth records in the US over the years 1990-2017 (over 97 million observations), we document substantial improvements in birth outcomes of mothers residing in counties with higher exposure to trade policy change. The exposed counties experienced sharp drops in employment specifically for manufacturing industries and revealed sharp reductions in a wide array of pollutants. A 1 percent reduction in tariff rates is associated with an 11.5 and 12.7 percentage point reduction in the likelihood of low birth weight and preterm birth, respectively.
Keywords: Trade Liberalization, Pollution, Air Quality, Health, Fetal Origin Hypothesis, Birth Outcomes, Panel Data, Environmental Health